Legal Protection For Third Parties Who Are Provided As Individual Guarantees By Fintech Peer-To-Peer Lending - Ferdiansyah Putra Manggala (Universitas Muhammadiyah Gresik, 2023)
The emergence of fintech companies is increasingly receiving attention from the public and regulators, namely the financial services authority (OJK) and Bank Indonesia (BI). This is stated in Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services. This regulation regulates information technology-based money lending and borrowing services or what is called peer to peer money lending. As of May 24 2021, the total number of fintech peer to peer lending or fintech lending providers registered and licensed with the OJK was 131 companies. In the case of a loan recipient applying for a loan on an online loan platform, the borrower will usually be asked to include an emergency contact as a condition for applying for a loan, but this is done without the permission of the third party who is used as an emergency contact. This resulted in losses for the emergency contact party due to terror from the lender as a result of the loan recipient experiencing late payments. LBH Jakarta received 1330 reports of loan victims from 25 provinces in Indonesia. One of them is Dian Siregar, who was a victim who was terrorized by an online loan where he received a short message from one of the KSP Rupiah Petir Pro loan applications after being made a guarantor by his friend without prior approval or confirmation.